Are Market-Based Conservation Schemes Gender-Blind? A Qualitative Study of Three Cases From Kenya. Issue 4 (2nd April 2016) - Kariuki, Juliet; Birner, Regina
ABSTRACT: Payments for Ecosystem Services (PES) and Reduced Emissions from Deforestation and Forest Degradation (REDD) are considered effective market-based conservation approaches. Surprisingly, limited evidence is conceptualized from a gendered perspective despite widespread knowledge of men's and women's roles as resource users. This study unravels this puzzle by exploring the extent to which three schemes in Kenya integrate gender in design and implementation. We adopt a combination of in-depth intrahousehold interviews, gender-disaggregated focus-group discussions, and key informant interviews to collect data from scheme members. With the exception of REDD, results reveal widespread gender exclusion despite gender-differentiated costs and benefits incurred by community members living around conservation areas. Gender blindness is considered to reflect economic rationale, property rights, and perception biases. We recommend a broader conceptualization of property rights beyond that of ownership to incorporate use rights and labor costs often incurred differently, but considerably by men and women.